Evaluation of Specialty Soybean Products and Organic Acids to Alter Nursery Dietary Acid-Binding Capacity-4 on Pig Performance and Fecal Dry Matter - Ethan B. Stas; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 300 pigs (241 × 600, DNA; initially 12.4 lb) were used to evaluate specialty soybean products and organic acids to alter the acid-binding capacity-4 (ABC-4) level of the diet on nursery pig performance and fecal dry matter (DM). At weaning, pigs were allotted to 1 of 6 dietary treatments. Diet 1 was formulated with 12.0% specialty soy protein concentrate (AX3 Digest; Protekta; Plainfield, IN), 1.06% citric acid, and 0.5% fumaric acid to achieve an ABC-4 of 223 meq/kg. Diets 2 and 3 were the same as diet 1 except citric and fumaric acid were reduced by 50 and 100% to achieve an ABC-4 of 280 or 338 meq/kg, respectively. Diets 4 and 5 were formulated with 50 and 100% replacement of specialty soy protein concentrate with enzymatically treated soybean meal (HP 300; Hamlet Protein; Findlay, OH) on a SID Lys basis with 1.06% citric acid and 0.5% fumaric acid to achieve 280 and 338 meq/kg, respectively. Diet 6 was a positive control with the same formulation as diet 5 except for the addition of 2,500 ppm of Zn from ZnO to achieve a diet ABC-4 of 410 meq/kg. The dietary treatment structure facilitated the comparison of an increase in the ABC-4 level (223 to 338 meq/kg), and the method achieve the change (decreasing acidifier vs. specialty soy protein concentrate replacement diets) as well as their interactions. Pigs were fed the experimental diet for 24 d postweaning (d 0 to 24) followed by a common diet for an additional 18 d. There were no significant (P>0.05) ABC-4 method × level interactions through the duration of the study. From d 0 to 10, pigs fed increasing ABC-4 had poorer (linear,P= 0.046) F/G. Pigs fed the decreasing acidifier diets had increased (P= 0.038) fecal percentage DM on d 17 than pigs fed the soy source replacement diets. During the experimental period (d 0 to 24), pigs fed the diet with ZnO had improved (P<0.05) BW, ADG, ADFI, and F/G compared to pigs fed diets without ZnO. In summary, ZnO was able to improve nursery pig performance when experimental diets were fed. Increasing the ABC-4 level and the method to do so had minimal effects on nursery pig performance. However, further investigation is warranted to determine if a lower ABC-4 level would provide more benefit.
Keywords: acid-binding capacity-4; specialty soy protein sources; nursery pig